Heidegger with Dewey: Mitsein, solicitude, and education - Ryan Krahn (Revista Filosofía UIS, 2007)
Contra claims that depict Martin Heidegger's Sein und Zeit as lacking an ethics of Others, I interpret the very Being of Dasein as Mitsein, ontology as ethics. On the basis of this ethical interpretation of Heideggerian ontology, I draw out the implications such an interpretation has on our ontic, solicitous comportment towards Others. I consider vorausspringen, a mode of positive solicitude, as opening  up the possibility of a certain pedagogical orientation that serves as a practical, institutional counterpart to Heidegger's ontology. I argue that this Heideggerian pedagogy is neither individualistic nor autocratic, but instead mirrors John Dewey's "directed freedom."